Investigasi DFT pada Ekstrak Tanaman Cengkeh dan Tembakau sebagai Inhibitor Korosi Hijau - Muhamad Akrom (Universitas Sarjanawiyata Tamansiswa, 2022)
In the present work, corrosion inhibition of Syzygium aromaticum and Nicotiana tabacum extract was studied by DFT method. Frontier molecular orbitals (FMO) plots, quantum chemical descriptors such as highest occupied molecular orbital energy (EHOMO), lowest unoccupied molecular orbital energy (ELUMO), energy gap (ΔE), dipole moment (l) and partial charge analysis were calculated. The results obtained show that the eugenol as extract of Syzygium aromaticum and nicotine as extract of Nicotiana tabacum acts as an effective green corrosion inhibitor. In general, nicotine has a better potential as an green corrosion inhibitor than eugenol based on chemical reactivity. However, further studies are needed to gain insight into the mechanism of corrosion inhibition through the study of the adsorption of eugenol and nicotine molecules on metal surfaces.